MENILIK HISTORIKAL PRAKTIK MODERASI BERAGAMA WALISONGO DI INDONESIA - Ningtyas, Dea Tara (Moderatio: Jurnal Moderasi Beragama, 2021)
Walisongo or Walisanga is known as a propagator of Islam in Java in the 14th century. They live in three important areas, namely the north coast of Java Island, namely Surabaya, Gresik, Lamongan and Tuban in East Java, then Demak, Kudus, and Muria in Central Java, then Cirebon in West Java.